Analisis Pelaksanaan P5 Tema Kearifan Lokal “Topeng Dalang Sumenep” Pada Siswa Kelas V Di SDN Pabian III - Mohammad Abrori; Farwa Al-Ifrah; RB. M. Dwitama Windrasana; Firman Ardiansyah Lukmana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of local wisdom "Topeng Dalang Sumenep" for fifth grade students at SDN Pabian III. The study used a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results showed that the implementation of P5 was carried out through eight stages involving museum visits, mask-making training, dance introduction, group exercises, and performances. Each stage was designed to strengthen the dimensions of the Pancasila Student Profile, such as mutual cooperation, creativity, critical thinking, and appreciation for diversity. This study also found several supporting factors, such as teacher support and facilities, as well as challenges in the form of limited time and funds. In conclusion, the implementation of P5 with this theme succeeded in increasing students' understanding of local culture while strengthening students' characters in accordance with Pancasila values.